2000
DOI: 10.1136/ard.59.7.521
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging, radiography, and scintigraphy of the finger joints: one year follow up of patients with early arthritis

Abstract: Objectives-To evaluate synovial membrane hypertrophy, tenosynovitis, and erosion development of the 2nd to 5th metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints by magnetic resonance imaging in a group of patients with rheumatoid arthritis (RA) or suspected RA followed up for one year. Additionally, to compare the results with radiography, bone scintigraphy, and clinical findings. Patients and methods-Fifty five patients were examined at baseline, of whom 34 were followed up for one year. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
0
10

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(160 citation statements)
references
References 35 publications
8
142
0
10
Order By: Relevance
“…This illustrates that the information on joint destruction provided by CR is associated with a considerable delay. In accordance with results of earlier studies (6)(7)(8)12), we observed that the sensitivity of MRI with respect to visualization of bone erosions was superior to that of CR. Furthermore, MRI detected erosive progression in more bones than did CR (i.e., MRI was more sensitive to change).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This illustrates that the information on joint destruction provided by CR is associated with a considerable delay. In accordance with results of earlier studies (6)(7)(8)12), we observed that the sensitivity of MRI with respect to visualization of bone erosions was superior to that of CR. Furthermore, MRI detected erosive progression in more bones than did CR (i.e., MRI was more sensitive to change).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies of patients with RA have shown that magnetic resonance imaging (MRI) detects more bone erosions than does CR (6)(7)(8). Due to the lack of long-term MRI followup studies, however, the time advantage offered by MRI compared with CR is unknown.…”
mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is more sensitive for the detection of synovitis and bone erosions in RA than are conventional radiography and clinical assessment (2)(3)(4). However, the specificity of the MRI findings in this context remains to be established.…”
mentioning
confidence: 99%
“…Until recently, imaging of the rheumatoid joint relied on radiologic (x-ray) measurement of cartilage and bone destruction which, while indicative of damage, often provides only limited information about the level of active synovial inflammation. Conventional whole-body bone scintigraphy relies on uptake of radioactive isotopes to regions of bone hyperemia and lacks sensitivity to disease activity over time (3). Although there have been exciting advances recently in the radiologic quantification of the inflamed synovium with the use of power Doppler ultrasound (4) and magnetic resonance imaging (5), the development of an imaging technology that could assess synovitis in multiple joints with simultaneous sensitivity to short-term changes would be a significant advance.…”
Section: Garrood and Costantino Pitzalismentioning
confidence: 99%